Government Digital Transformation: Understanding the Role of Government Social Media - Mita Noviani; Hasnawati Hasnawati (Eduvest - Journal of Universal Studies, 2025)
MSMEs have a strategic role in the Indonesian economy, with significant contributions to GDP and employment. In the digital era, social media has become an important tool for communication and interaction between government and society. This research aims to understand the role of government social media in digital transformation, specifically through a case study on the Ministry of Cooperatives and SMEs towards MSME players in Jakarta. The research method used is a quantitative approach using a questionnaire distributed to 181 respondents who are MSME players in Jakarta. This study explores the influence of reachability, information quality, and social media engagement as independent variables on public trust in government social media agencies as the dependent variable. The results of multiple linear regression analysis show that these three factors have a significant positive influence on public trust. This finding supports cultivation theory which states that consistent and high-quality media exposure can shape positive public perceptions. Recommendations are given to the government to improve outreach, information quality, and active engagement on social media to build trust and support the growth of MSMEs.